2017
DOI: 10.1017/s0022215117001554
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian tube dysfunction leading to middle-ear pathology in patients on chronic mechanical ventilation

Abstract: Middle-ear pathology is common in patients on chronic mechanical ventilation via tracheostomy tube. The highest prevalence was in those with impaired consciousness or cognition, and oral feeding appeared protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…While chronic adenoiditis and rhinosinusitis are known risk factors for ETD, these causes of nasal airway obstruction also contribute an inflammatory component to the dysfunction of the Eustachian tube. Although some studies have demonstrated that increased nasal obstruction from purely anatomic causes, such as septal deviation (Kaya et al, 2018) and inferior turbinate hypertrophy (Harju, et al, 2017), can contribute to ETD, other studies show little to no effect in patients with tracheostomy (Meric et al, 2012) or laryngectomy (Ilan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While chronic adenoiditis and rhinosinusitis are known risk factors for ETD, these causes of nasal airway obstruction also contribute an inflammatory component to the dysfunction of the Eustachian tube. Although some studies have demonstrated that increased nasal obstruction from purely anatomic causes, such as septal deviation (Kaya et al, 2018) and inferior turbinate hypertrophy (Harju, et al, 2017), can contribute to ETD, other studies show little to no effect in patients with tracheostomy (Meric et al, 2012) or laryngectomy (Ilan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in techniques and surgical instruments to minimize the need for resection and damage to adjacent structures in the skull base may improve the postoperative quality of life 19 . The Eustachian tube is of critical importance for middle ear function including pressure regulation and hearing 20 . Although tympanostomy and tube insertion can solve the pressure dysfunction, potential hearing loss and worsened middle ear function are still of concern 13,21 .…”
Section: Discussionmentioning
confidence: 99%
“…19 The Eustachian tube is of critical importance for middle ear function including pressure regulation and hearing. 20 Although tympanostomy and tube insertion can solve the pressure dysfunction, potential hearing loss and worsened middle ear function are still of concern. 13,21 Therefore, efforts to preserve the function of the Eustachian tube are desirable.…”
Section: Discussionmentioning
confidence: 99%